Learn to Program with Python 3 A Step-by-Step Guide to Programming - Kalb, Irv (Apress, 2018)
Move from zero knowledge of programming to comfortably writing small to medium-sized programs in Python. Fully updated for Python 3, with code and examples throughout, the book explains Python coding with an accessible, step-by-step approach designed to bring you comfortably into the world of software development. Real-world analogies make the material understandable, with a wide variety of well-documented examples to illustrate each concept. Along the way, you'll develop short programs through a series of coding challenges that reinforce the content of the chapters. Learn to Program with Python 3 guides you with material developed in the author's university computer science courses. The author's conversational style feels like you're working with a personal tutor. All material is thoughtfully laid out, each lesson building on previous ones.